Dispute settlement reports 2018. World Trade Organization. (Cambridge University Press, 2020)
The Dispute Settlement Reports are the WTO authorized and paginated reports in English. They are an essential addition to the library of all practicing and academic trade lawyers and needed by students worldwide taking courses in international economic or trade law. DSR 2018: Volume 10 reports on Australia - Certain Measures Concerning Trademarks, Geographical Indications and Other Plain Packaging Requirements Applicable to Tobacco Products and Packaging (WT/DS435, WT/DS441, WT/DS458, WT/DS467) and United States - Certain Methodologies and their Application to Anti-Dumping Proceedings Involving China - Arbitration under Article 21.3(c) of the DSU (WT/DS471).